Biosorption of Chromiun in Batik Wastewater Using SCOBY Microbial Biomass: A Sustainable Bioremediation Approach - Nur Lu’lu Fitriyani; Dina Adelia; Slamet Budiyanto; Ristiawati; Jaya Maulana; Muhammad Choiroel Anwar (Advance Sustainable Science Engineering and Technology, 2025)
Batik wastewater poses an environmental threat due to hazardous heavy metals like lead, cadmium, and chromium (Cr). This study investigated the effectiveness of SCOBY (Symbiotic Culture of Bacteria and Yeast), a microbial consortium from kombucha production, in reducing Cr levels in batik wastewater. SCOBY is a promising biosorbent for heavy metals. The research aimed to assess SCOBY's ability to decrease Cr contamination in different types of batik wastewater (hand-drawn, stamped, and printed) over varying incubation times. Using a quasi-experimental approach, wastewater samples were collected from small and medium industries in Pekalongan City. Results showed that SCOBY effectively reduced Cr levels across all batik wastewater types and incubation periods. The most significant reduction occurred at 3 hours of incubation. Specifically, Cr levels decreased by 53% in hand-drawn batik wastewater, 44% in stamped batik wastewater, and an impressive 71% in printed batik wastewater. These findings suggest that SCOBY treatment is a viable and effective alternative for managing batik wastewater.